1986
DOI: 10.1038/322747a0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and discontinuous protein antigenic determinants

Abstract: Protein antigenic determinants have been classified as continuous or discontinuous. The continuous determinants are composed of residues which are local in the polypeptide sequence, while discontinuous determinants consist of residues from different parts of the sequence, brought together by the folding of the protein to its native structure. Searches made for protein determinants using peptide fragments which compete with protein-antibody complex formation, or peptides that can be used to raise antibodies whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
296
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(309 citation statements)
references
References 14 publications
10
296
1
2
Order By: Relevance
“…All these results would be in favour of an exposed, rigid, continuous epitope, devoid of regular secondary structure. This does not agree with observations showing that antibodies often tend to recognize short peptides or discontinuous epitopes when the peptides correspond to mobile segments of a native protein [18,24,32-341, but does agree with those studies showing that large surface exposures [35 -371 and protruding loops [38] are the best antigenic regions.…”
contrasting
confidence: 51%
“…All these results would be in favour of an exposed, rigid, continuous epitope, devoid of regular secondary structure. This does not agree with observations showing that antibodies often tend to recognize short peptides or discontinuous epitopes when the peptides correspond to mobile segments of a native protein [18,24,32-341, but does agree with those studies showing that large surface exposures [35 -371 and protruding loops [38] are the best antigenic regions.…”
contrasting
confidence: 51%
“…According to their pattern of reactivity the anti-topo II a-positive sera were scored for epitope complexity as follows: 1 for contiguous, 2 for discontiguous and 3 for highly conformational epitopes in agreement with previous studies [18][19][20]32,33]. The analysis of correlation between the score of epitope complexity and the clinical data was undertaken both by means of Kendall's coefficient of correlation and by Kruskal-Wallis one-way ANOVA test to assay the variance of the three groups for each of the clinical parameters.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, analysis of the protein surfaces suggests that all determinants are discontiguous to some extent, and that cross-reacting peptides mimic only the primary interaction site [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports 18,19 have suggested that the majority of antibodies recognize conformational epitopes consisting of amino acids that are brought together in space by the folding of several chains of the protein target. In contrast, the method described here relies on antibodies binding to linear epitopes, while the conformational epitopes are only recovered on the last antigen matrix.…”
Section: Discussionmentioning
confidence: 99%